2019
DOI: 10.1002/ijc.32313
|View full text |Cite
|
Sign up to set email alerts
|

EPHA2 blockade reverses acquired resistance to afatinib induced by EPHA2‐mediated MAPK pathway activation in gastric cancer cells and avatar mice

Abstract: Afatinib is a pan‐HER inhibitor approved for specific types of lung cancer. We explored antitumor activity, predictive biomarkers and the potential mechanisms underlying antitumor effect and acquired resistance of afatinib in gastric cancer (GC) in vitro and in vivo. Five human GC cell lines and eight patient‐derived xenograft (PDX) models with clear molecular profiling were used to evaluate the antitumor activity and mechanisms of afatinib. The ErbB family and downstream PI3K/AKT/mTOR and mitogen‐activated pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 36 publications
(72 reference statements)
0
18
0
1
Order By: Relevance
“…Y. Wang et al, 2013), and is involved in oncogenesis of various malignancies of the digestive system (Z. Chen et al, 2019;Gao et al, 2017;. In our outcomes, LY294002 was used for rescue experiments.…”
Section: Cst1 Expression Promoted Hcc Tumor Growth and Metastasismentioning
confidence: 99%
“…Y. Wang et al, 2013), and is involved in oncogenesis of various malignancies of the digestive system (Z. Chen et al, 2019;Gao et al, 2017;. In our outcomes, LY294002 was used for rescue experiments.…”
Section: Cst1 Expression Promoted Hcc Tumor Growth and Metastasismentioning
confidence: 99%
“…These miRNAs exert tumor-suppressive effects by repressing oncogenes in HCC [73][74][75]. miRNA deregulation is an early event that can be detected in premalignant liver dysplastic nodules and can further accumulate during liver carcinogenesis [76][77][78][79].…”
Section: Discussionmentioning
confidence: 99%
“…EPHA2 is a member of the ephrin receptor subfamily of protein tyrosine kinases, and EFNA1 (ephrin A1) is its ligand. Recent studies considered the EPHA2 signalling pathway as a target of cancer therapy, and revealed that blocking EPHA2 reversed the acquired resistance of gastric cancer cells to afatinib and inhibit the proliferation of small cell lung cancer cells 31,32 . In ESCC, EFNA1 and EPHA2 were upregulated, and their overexpression was correlated with short overall survival in patients 17,33,34 .…”
Section: Discussionmentioning
confidence: 99%